Is global ozone recovering? - Steinbrecht, Wolfgang; Hegglin, Michaela I.; Harris, Neil; Weber, Mark (Elsevier, 2018)
Thanks to the Montreal Protocol, the stratospheric concentrations of ozone-depleting chlorine and bromine have been declining since their peak in the late 1990s. Global ozone has responded: The substantial ozone decline observed since the 1960s ended in the late 1990s. Since then, ozone levels have remained low, but have not declined further. Now general ozone increases and a slow recovery of the ozone layer is expected. The clearest signs of increasing ozone, so far, are seen in the upper stratosphere and for total ozone columns above Antarctica in spring. These two regions had also seen the largest ozone depletions in the past. Total column ozone at most latitudes, however, does not show clear increases yet. This is not unexpected, because the removal of chlorine and bromine from the stratosphere is three to four times slower than their previous increase. Detecting significant increases in total column ozone, therefore, will require much more time than the detection of its previous decline. The search is complicated by variations in ozone that are not caused by declining chlorine or bromine, but are due, e.g., to transport changes in the global Brewer–Dobson circulation. Also, very accurate observations are necessary to detect the expected small increases. Nevertheless, observations and model simulations indicate that the stratosphere is on the path to ozone recovery. This recovery process will take many decades. As chlorine and bromine decline, other factors will become more important. These include climate change and its effects on stratospheric temperatures, changes in the Brewer–Dobson circulation (both due to increasing CO2), increasing emissions of trace gases like N2O, CH4, possibly large future increases of short-lived substances (like CCl2H2) from both natural and anthropogenic sources, and changes in tropospheric ozone.
Keywords: Ozone; Stratosphere; Climate change; Montreal Protocol